"Olha a terra, meu amigo, como é que ela é?": tradução, análise e herança cultural do mito mesopotâmico Etana - Fátima Rosa, Maria de (Lusitania sacra, 2024)
The article aims to present a translation of the Myth of Etana from the original Akkadian into Portuguese. With this intent, an accurate linguistic study was carried out, followed by the analysis of the main thematic, namely: the importance of progeny in royal ideology, the role of the divine oath and of god Šamaš in it, and the stages of the journey of King Etana and the eagle, the main protagonists of the narrative. Bearing in mind that the composition inspired numerous other tales from the ancient world, which are known presently, this study also addresses its cultural legacy.